2019
DOI: 10.3390/math7040326
|View full text |Cite
|
Sign up to set email alerts
|

The General Least Square Deviation OWA Operator Problem

Abstract: A crucial issue in applying the ordered weighted averaging (OWA) operator for decision making is the determination of the associated weights. This paper proposes a general least convex deviation model for OWA operators which attempts to obtain the desired OWA weight vector under a given orness level to minimize the least convex deviation after monotone convex function transformation of absolute deviation. The model includes the least square deviation (LSD) OWA operators model suggested by Wang, Luo and Liu in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…where the generating functions are absolutely continuous. Hong and Han [10] recently proposed the general least convex deviation model with a given orness level, as follows:…”
Section: The General Model For the Least Convex Disparity Rim Quantifmentioning
confidence: 99%
See 2 more Smart Citations
“…where the generating functions are absolutely continuous. Hong and Han [10] recently proposed the general least convex deviation model with a given orness level, as follows:…”
Section: The General Model For the Least Convex Disparity Rim Quantifmentioning
confidence: 99%
“…One of the important topics in the theory of ordered weighted averaging (OWA) operators is the determination of the associated weights. Several authors have suggested a number of methods for obtaining associated weights in many areas, such as decision-making, approximate reasoning, expert systems, data mining, as well as fuzzy systems and control [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Yager [15] proposed regular increasing monotone (RIM) quantifiers as a method for obtaining OWA weight vectors through fuzzy linguistic quantifiers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In domains where information fusion/integration or multi-factorial evaluation is needed, an aggregation process is necessary to combine multiple sources of infor-mation into a global result so that in the final decision, all the individual sources of information are taken into account [1]. For example, in medicine, diagnosis or measurement can rarely be decided based on an individual criterion.…”
Section: Introductionmentioning
confidence: 99%
“…In general, smooth manifolds in function optimization serve to conveniently represent non-linear constraints. Constrained optimization arises in several branches of science, ranging from applied mathematics [14][15][16] to information sciences [14,17,18]. In [19,20], optimization-based mean-computation problems over the space of the symmetric positive-definite matrices, the special Euclidean group and the space of unipotent matrices were studied.…”
Section: Introductionmentioning
confidence: 99%